1987
DOI: 10.1093/jac/20.6.893
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and treatment of rhinovirus colds with zinc gluconate lozenges

Abstract: Following a tolerance study, double-blind placebo controlled trials were conducted to determine the prophylactic effect of zinc gluconate lozenges on rhinovirus challenge and, in a third study, their therapeutic efficacy when given at the start of colds caused by virus inoculation was tested. In the prophylaxis study a total of 57 volunteers received lozenges of either zinc gluconate (23 mg) (29 volunteers) or matched placebo (28 volunteers) every 2 h while awake during a period of four and a half days. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 8 publications
2
93
1
Order By: Relevance
“…Eby described these effects as local, not systemic. Similar results rapidly followed with a 1987 report by the British Medical Research Council (MRC) Common Cold Unit [3].…”
Section: Introductionsupporting
confidence: 84%
“…Eby described these effects as local, not systemic. Similar results rapidly followed with a 1987 report by the British Medical Research Council (MRC) Common Cold Unit [3].…”
Section: Introductionsupporting
confidence: 84%
“…This is further suggested by another study, which found a significant reduction of symptoms when a non-chelating formulation was used. 7 The present study was carried out to test the hypothesis that pleasant-tasting ZGG lozenges that release 93% of the ionic zinc into saliva may produce similar efficacy to that originally reported by Eby et al 1 …”
Section: Introductionmentioning
confidence: 77%
“…The remaining four trials either measured but did not report the outcome 26,29 or reported the proportion of symptomatic patients on each day. 38,39 Eight trials (n = 934) could be pooled in the meta-analysis ( Figure 2).…”
Section: Duration Of Symptomsmentioning
confidence: 99%